Internal and External R&D: A Sample Selection Approach - Marco Vivarelli; Claudio Piga (Max Planck Institute for Research into Economic Systems, 2003)
This study explicitly takes into account that the decision to enter into an external R&D relationship is related to an antecedent decision to carry out R&D. This calls for a methodological approach that, at the same time, permits the joint analysis of the determinants of the two decisions and corrects for the sample selectivity that is intrinsic in the analysis of external R&D. Based on a sample of Italian manufacturing firms, the results confirm the need to consider explicitly the selectivity issue in the empirical analysis of external R&D. Another contribution made by this study is the managerial implications that can be derived from its empirical model, which provide a better understanding of the factors determining a firm's decision to engage in R&D both independently and with external partners.
Keywords: O32; L2; 330; Cooperative R&D; vertical relationships; R&D management; bivariate probit; selectivity; Forschung; Betriebliche Forschung; Outsourcing; Forschungskooperation; Theorie; Schätzung; Italien